Reformasi Hukum Pajak Indonesia Dalam Menghadapi Ekonomi Digital (Studi Atas Nexus Dan Significant Economic Presence) - Amalia, Rizki Fitri; Sudarna, Sudarna (Lex Librum : Jurnal Ilmu Hukum, 2025)
The development of the digital economy has fundamentally transformed global economic interactions, enabling foreign digital companies to generate profits from Indonesia without having a physical presence. This situation poses challenges in collecting Income Tax, particularly concerning base erosion and tax leakage. This study aims to analyze Indonesia's tax law reform in strengthening the digital nexus through the implementation of the Significant Economic Presence (SEP) concept and to identify normative and practical obstacles in its implementation. The research employs normative legal methods with statutory, conceptual, and comparative approaches. The results indicate that the SEP broadens the nexus criteria from physical presence to significant economic presence, thereby strengthening Indonesia’s taxing rights and preventing cross-border profit shifting. However, SEP implementation faces normative obstacles, including conflicts with Double Tax Avoidance Agreements (DTAAs), the absence of a global consensus, and limited technical parameters. Practical obstacles include restricted access to transaction data, difficulty in enforcing tax obligations on entities without legal presence in Indonesia, low compliance from digital companies, and limited international cooperation. The study recommends strengthening the legal framework and international harmonization, as well as enhancing digital tax administration capacity through technology and cross-border collaboration.